Effect of a perioperative immune-enhancing diet in clean-contaminated head and neck cancer surgery: A randomized controlled trial. (September 2021) - Sittitrai, Pichit; Ruenmarkkaew, Donyarat; Booyaprapa, Somkamol; Kasempitakpong, Boosita
Abstract: Background: Malnutrition is a common problem in head and neck cancer patients and is associated with an increased risk of postoperative complications and prolonged length of hospital stay (LOS). The purpose of this study was to evaluate the effect of an immune-enhancing diet with supplementary arginine, glutamine, and fish oil in clean-contaminated head and neck cancer surgery. Materials and methods: A randomized controlled trial study in clean-contaminated head and neck cancer surgery patients was conducted. Patients undergoing surgery received either an immune-enhancing diet or hospital-prepared blenderized diet 7 days preoperatively and 14 days postoperatively. Clinical outcomes (mucocutaneous fistula, wound infection, general infection, LOS, and hospital costs) and nutritional parameters (body weight, prealbumin, transferrin, and albumin) were compared between the two groups. Results: 116 patients were included in the analysis, 60 in the immune-enhancing diet group and 56 in the blenderized diet group. There was a significant association between the immune-enhancing diet and the decrease in fistula rate (8.3 % vs. 23.2 %, p = 0.039), LOS (24 days vs. 29 days, p = 0.043), hospital costs (6312 US dollars vs. 7461 US dollars, p = 0.048), and higher prealbumin level on postoperative day 7 and 14 (p = 0.015 and 0.001, respectively) and transferrin level on postoperative day 14 (p = 0.047). In addition, the immune-enhancing diet also had a positive effect on body weight on postoperative day 14 (p = 0.028). However, there was no difference in nutrition-related adverse events between the two groups. Conclusion: The administration of a perioperative diet containing arginine, glutamine, and fish oil in clean-contaminated head and neck cancer surgery patients led to a significant reduction in mucocutaneous fistula, LOS, and hospital costs. Results also indicated improved nutritional status, including body weight, prealbumin, and transferrin levels. Highlights: Malnutrition in head and neck cancer patients is associated with an increased risk of postoperative complications. An immune-enhancing diet is thought to modify the immune system and inflammatory responses. Perioperative immune-enhancing diet could reduce mucocutaneous fistula, postoperative hospital stay, and hospital costs. Preoperative immune-enhancing nutrition for more than 7 days is expected to result in greater benefits.